Bridging Normative Democratic Theory and Internet Technologies: A Proposal for Scaling Citizen Policy Deliberations. Issue 4 (December 2013) - Liston, Vanessa; Harris, Clodagh; O'Toole, Mark
<x xml:space="preserve">Abstract</x> This article presents an experimental model for citizen deliberation that bridges the gap between developments in normative deliberative theory, and online participation and deliberation in practice. The Social Web for Inclusive and Transparent democracy (SOWIT) model is designed for integration into policy‐making processes. It is currently being developed in consultation with citizens, civil society organizations, and Councilors in an Irish local authority and will be implemented in 2014. Our approach is rooted in Dryzek and Niemeyer's (Dryzek and Niemeyer [2008]. American Political Science Review 102(4): 481–93) innovations in discursive representation and meta‐consensus as well as Bächtiger et al.'s (Bächtiger et al. [2010]. Journal of Political Philosophy 18: 32–63) sequential approach to deliberation. SOWIT pioneers a dynamic implementation of a meta‐consensus framework for structuring and incentivizing policy deliberations. In this article, we present the model, explain its normative rationale, and outline the experimental framework.